2021
DOI: 10.31933/dijemss.v2i3.764
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Teacher Sertification on Teacher Performance in School

Abstract: Teacher certification is one form of implementation of Law Number 14 of 2005 concerning Teachers and Lecturers by providing teacher certificates to teachers who have met certain requirements, namely having academic qualifications, competence, being physically and mentally healthy, and having the ability to realize national educational goals, followed by an increase in decent welfare. Teacher certification aims to increase knowledge, performance, creativity, and be able to carry out other main tasks and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…In other words, financing is funding issued to support planned investments to achieve predetermined goals. Funding is a resource that can directly support the effectiveness and efficiency of education management (Sudarmono et al, 2021). Funding for education is basically a process of allocating resources to activities or programs for the implementation of educational operations or in the process of teaching and learning in the classroom.…”
Section: Literature Review Educational Financing Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, financing is funding issued to support planned investments to achieve predetermined goals. Funding is a resource that can directly support the effectiveness and efficiency of education management (Sudarmono et al, 2021). Funding for education is basically a process of allocating resources to activities or programs for the implementation of educational operations or in the process of teaching and learning in the classroom.…”
Section: Literature Review Educational Financing Managementmentioning
confidence: 99%
“…Because it is implemented not only in accordance with government regulations but also sharia values and good Islamic examples (Shaturaev, 2021). Research conducted by Sudarmono et al (2021) revealed that education funding must refer to the standard education unit costs that have been set by a Ministerial Regulation based on the proposal of the National Education Standards Agency (BSNP). This education financing standard is expected to be used as a reference in the implementation of education at every level of education.…”
Section: Introductionmentioning
confidence: 99%
“…(Anwar, 2020) sehingga citra pendidik professional ini sangat melekat pada diri seorang guru, dan guru dinyatakan layak sebagai panutan bagi masyarakat. Menurut (Sudarmono; Dalam mengikuti sertifikasi guru memiliki syarat yang harus dipenuhi secara kualifikasi yang telah ditentukan oleh kementerian. Para guru harus melalui ujian untuk memperoleh serdik atau disebut dengan sertifikat pendidik, apabila guru telah dinyatakan lulus dalam ujian tersebut maka guru berhak mendapatkan tunjangan dari serdik itu.…”
Section: Pendahuluanunclassified
“…Pasal 11 ayat (1) Menentukan serdik atau lebih dikenal sertifikat pendidika dimaksud didalam pasal 8 akan diberikan kepada intruktur yang tentunya memenuhi standar kualifikasi sebagai pendidik profesional., (Latiana, 2019). Manfaat yang sangat amat dapat diharapkan adanya pengelolaan sertifikasi ini akan membuat Hasrat para guru meningkatkan kualitas sebagai tenaga pengajar yang pro dan membuat para guru berlomba lomba untuk mendapatkan tunjangan tersebut (Sudarmono;.…”
Section: Pendahuluanunclassified